Pilot study on surgical tissue collection for development of functional hospital-based biobank model - Ahmad Affandi, Khairunisa; Mahno, Noor Ezmas; Mohd Rodzi, Muhammad Qamarul Izzat; Abd Rahman, Nurul Azirah; Lee, Lian Wei; Abdul Mun'im, 'Aatikah Rashidah (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2026)
Introduction: Hospital-based biobanks play a critical role in translational cancer research by providing high-quality human biospecimens linked with clinical data. The Biobank Unit under the Department of Pathology and Laboratory Medicine, SASMEC @IIUM is in the early stages of establishment and refining its operational processes. A three-month pilot project was conducted in collaboration with the breast and endocrine surgical team to develop a functional repository model and establish a practical workflow for biobank tissue collection. Materials and Methods: Eligible patients were identified through operating theatre lists and surgical clinic referrals. Information sheets and written biobank consent forms were provided during routine pre-operative counselling. Surgical specimens from consented patients were transported to the laboratory, where surplus tissue was harvested, processed, and stored as formalin-fixed paraffin-embedded blocks in the designated biobank facility. A secure log documenting sample identifiers, diagnoses, and limited clinical information was maintained. Results: A total of 28 patients were approached and all provided consent (100% consent rate). Three cases were suitable for banking. Specimens were handled and processed promptly to preserve sample integrity. Early feedback highlighted improved communication and clearer role delineation among teams. Operational gaps were identified, prompting targeted refinements to streamline the workflow. Conclusion: This pilot study provided a functional institutional repository model for prospective surgical tissue collection. The model can be expanded to other clinical units at SASMEC @IIUM for future collaborative research.